RITUXIMAB IN TREATMENT OF A PATIENT WITH GRANULOMATOSIS WITH POLYANGIITIS – A CASE REPORT - Bojadzioska, Maja; Guchev, Filip; Antova, Dubravka; Karadzova-Stojanoska, Anzhelika; Vidinikj, Sonja; Damjanovska Krstikj, LJubinka; Sandevska, Emilija; Vasilevska, Ana; Petrova, Sanja; Tofiloska, Valentina; Curakova Ristovska, Elena; Vejseli, Ron (Македонско лекарско друштво = Macedonian medical association/De Gruyter, 2024)
ANCA-associated vasculitis (AAV) is a necrotizing vasculitis with few or no immune deposits that can affect predominantly small vessels. It can affect ve-ssels in every organ and tissue of the body; the clinical manifestations of the disease are extremely variable. B-cells are of major importance in the disease patho¬ge¬nesis as precursors of ANCA-producing plasma cells and, possibly, also as antigen-presenting and cytokine-producing cells. Therefore, rituximab, a monoclonal anti¬body drug causing partial B-cell depletion, has emerged as a powerful option in the treatment of AAV such as granulomatosis with polyangiitis. We present the case of a 25-year-old female diagnosed with granu-lomatosis with polyangiitis and treated with rituximab and high-dose corticosteroids.
РИТУКСИМАБ ВО ТРЕТМАН НА ПАЦИЕНТ СО ГРАНУЛОМАТОЗА И ПОЛИАНГИИТИС – ПРИКАЗ НА СЛУЧАЈ
Keywords: ANCA; vasculitis; rituximab; treatment; remission